x(x+1)(x-4)+4(x+1)=0

Simple and best practice solution for x(x+1)(x-4)+4(x+1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+1)(x-4)+4(x+1)=0 equation:


Simplifying
x(x + 1)(x + -4) + 4(x + 1) = 0

Reorder the terms:
x(1 + x)(x + -4) + 4(x + 1) = 0

Reorder the terms:
x(1 + x)(-4 + x) + 4(x + 1) = 0

Multiply (1 + x) * (-4 + x)
x(1(-4 + x) + x(-4 + x)) + 4(x + 1) = 0
x((-4 * 1 + x * 1) + x(-4 + x)) + 4(x + 1) = 0
x((-4 + 1x) + x(-4 + x)) + 4(x + 1) = 0
x(-4 + 1x + (-4 * x + x * x)) + 4(x + 1) = 0
x(-4 + 1x + (-4x + x2)) + 4(x + 1) = 0

Combine like terms: 1x + -4x = -3x
x(-4 + -3x + x2) + 4(x + 1) = 0
(-4 * x + -3x * x + x2 * x) + 4(x + 1) = 0
(-4x + -3x2 + x3) + 4(x + 1) = 0

Reorder the terms:
-4x + -3x2 + x3 + 4(1 + x) = 0
-4x + -3x2 + x3 + (1 * 4 + x * 4) = 0
-4x + -3x2 + x3 + (4 + 4x) = 0

Reorder the terms:
4 + -4x + 4x + -3x2 + x3 = 0

Combine like terms: -4x + 4x = 0
4 + 0 + -3x2 + x3 = 0
4 + -3x2 + x3 = 0

Solving
4 + -3x2 + x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 2L+2*(12-L)= | | 4(7x+2)=-300 | | 3b^2-4b-126=0 | | 8x-3=5+4y | | 5.50+6.50(2x)=351.50 | | 7(3x+6)=-189 | | 5/2=9 | | 2n^3+4n^2-7and-n^3+8n-9= | | 3+2y=32 | | 6-(1x+10)=42 | | 10s= | | 6(8-t)+11=-11(t-4)-7 | | 15-x=6x | | 4x^2+7x-92=0 | | 4-4x^2-4y^2+8xy=0 | | 5s= | | 8x+3y=80 | | 2/7k-3/7=-19/8 | | -7y+13=223 | | 5+2y=48 | | 8x+5=8x-6 | | 8.9x+9-1.9x=2 | | 1/8x-2 | | p(3p+1)(3p-1)= | | 55+(2x-49)+90+x=180 | | 13c+40=ac-20+c | | 3x-(4x+9)=5x-45 | | 15x-13=9x-6 | | 8x-3=5+44 | | 2x^2-3x-170= | | 2x-49+55-90+x=180 | | 2w+2*(5+w)=150 |

Equations solver categories